2018
DOI: 10.1093/ptj/pzy010
|View full text |Cite
|
Sign up to set email alerts
|

Function, Shoulder Motion, Pain, and Lymphedema in Breast Cancer With and Without Axillary Web Syndrome: An 18-Month Follow-Up

Abstract: AWS occurs in approximately 50% of women following breast cancer surgery. It can persist for 18 months and potentially longer, develop beyond the early postoperative time period, and reoccur after resolution. Clinicians need to be aware of the chronicity of AWS and its association with reduced range of motion and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 27 publications
3
70
3
Order By: Relevance
“…AWS most commonly develops 2–8 weeks following breast cancer surgery 14,7. However, recent studies have shown that AWS can occur months to years later and can also resolve and then relapse 2,7…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AWS most commonly develops 2–8 weeks following breast cancer surgery 14,7. However, recent studies have shown that AWS can occur months to years later and can also resolve and then relapse 2,7…”
Section: Introductionmentioning
confidence: 99%
“…One study had a prevalence of AWS of 50% at 18 months,2 and the other had a 51% incidence in the 8 weeks11 following surgery. The incidence is higher in surgery with ALND (36%–72%)1,2,4,7,9,10 compared with surgery with sentinel lymph node biopsy (SNB) (11%–58%) 1,4,7,10. For reasons that are not clear, the incidence of AWS is highest in patients who have a prior or contemporaneous contralateral prophylactic mastectomy (86%) 2.…”
Section: Introductionmentioning
confidence: 99%
“…Complicating things further, depending upon the extent of tissue removal and damage from the surgery [1,12,14] and radiation treatment [9,13,20,21] multiple fascial slings [17] may have been disrupted, creating a ripple effect on biomechanics of the entire body, reaching far beyond the shoulder. To date, there has been very little attention focused on soft tissue alterations [5,6,10,15] which are more likely to be the causative origin of joint dysfunctions. We propose these soft tissue changes can create systemic shifts in patient function due to effects on the fascial slings, resulting in altered length tension relationships in muscle-tendon complexes with negative implications in proprioception as joint loading is secondarily affected possibly disrupting the entire nervous system.…”
Section: Functional Limitations and Dysfunctional Presentationsmentioning
confidence: 99%
“…These patients can be treated more conservatively with similar outcomes, but without complications, commonly accompanying radical surgery (Huang et al, 2016, Choi et al, 2018. A complete axillary lymph node dissection in combination with a damage of lymphatic vasculature frequently results in lymphedema or axillary web syndrome, conditions which are potentially mutilating and can lead to disability (Gillespie et al, 2018, Koehler et al, 2018. Highly advantageous is that sentinel lymph node biopsy has a widespread application in the management of multiple oncological conditions, though in our review paper, we focus specifi cally on invasive breast cancer.…”
Section: Introductionmentioning
confidence: 99%